Highly expressed of SERPINA3 indicated poor prognosis and involved in immune suppression in glioma - Qing Yuan; Song‐Quan Wang; Guang‐Tao Zhang; Jie He; Zhi‐Dan Liu; Ming‐Rong Wang; Hong‐Qing Cai; Jing‐Hai Wan (Immunity, Inflammation and Disease, 2021)
Abstract Introduction The prognosis of patients with glioma is dismal. It has been reported that Serpin peptidase inhibitor clade A member 3 (SERPINA3) is associated with the mobility and invasion of tumor cells. Our study was designed to explore the value of SERPINA3 messenger RNA (mRNA) expression in the biological process, prognosis, and immune significance in glioma. Methods We analyzed the biological functions of SERPINA3 through data from the Chinese Glioma Genome Atlas databases. Differentially expressed genes and enrichment analysis were performed and correlations between SERPINA3 expression and immune cell infiltration were analyzed. Further, we validated the expression and the survival prediction role of SERPINA3 by using tissue microarrays and RNAscope in situ hybridization in 321 gliomas. The correlations between the expression and clinical‐pathological parameters as well as other biomarkers were examined. Results Univariate and multivariate regression both indicated that the level of SERPINA3 transcript represented an independent prognostic factor. High levels of SERPINA3 correlated with poor survival in patients with glioma. Expression of SERPINA3 mRNA was observed positively correlated with MCM6, IGFBP2, and FKBP10. Enrichment analysis showed SERPINA3 mainly enriched in immune‐related terms and signaling pathways including MAPK, TNF, P53, PI3K‐Akt, nuclear factor‐κB. Immune infiltration analysis further declare the SERPINA3 expression negatively correlated with levels of Macrophages M1, native CD4+ T cell, monocytes, and Mast cell activated. And overexpression of SERPINA3 correlated with low CD4+ T cell infiltration in glioma tissues. Conclusions SERPINA3 may play a key role in the biological process of glioma cells especially in immune suppression activities. SERPINA3 may serve as an independent survival prediction factor in glioma patients.